2019
DOI: 10.3390/w11061236
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change Impacts on Extreme High and Low Flows: An Improved Bottom-Up Approach

Abstract: A quantitative assessment of the likelihood of all possible future states is lacking in both the traditional top-down and the alternative bottom-up approaches to the assessment of climate change impacts. The issue is tackled herein by generating a large number of representative climate projections using weather generators calibrated with the outputs of regional climate models. A case study was performed on the South Nation River Watershed located in Eastern Ontario, Canada, using climate projections generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that, hydrological processes of several main basins in Tianshan and Kunlun Mountains have been significantly influenced by climate change [4]. Extreme precipitation events have the potential to aggravate floods and droughts [5][6][7], while the continuous rise in air/surface temperature may lead to the increasing snow melting and evapotranspiration (ET) in such mountainous river basins [8]. Understanding variations in historical discharge extremes and evaluating future changes will greatly contribute to flood hazard control and water resource management in inland river basins [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that, hydrological processes of several main basins in Tianshan and Kunlun Mountains have been significantly influenced by climate change [4]. Extreme precipitation events have the potential to aggravate floods and droughts [5][6][7], while the continuous rise in air/surface temperature may lead to the increasing snow melting and evapotranspiration (ET) in such mountainous river basins [8]. Understanding variations in historical discharge extremes and evaluating future changes will greatly contribute to flood hazard control and water resource management in inland river basins [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Papers [13,14] reported research on droughts. Future droughts under a range of climate scenarios were examined in [13].…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…This research identified the season, direction, and magnitude of changes in the length of dry spells for different parts of the Southeast United States. The effects of droughts on both low flows and floods were reported in [14]. This paper presented a novel method to create a super-ensemble of future climate series, which was then used to derive flooding and drought indices.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…Instrumental records are typically only a few decades long and are not available everywhere (e.g. Alexander, 2016). Reanalysis products are increasingly employed to estimate extremes, as they blend observational datasets with model simulations into spatially and temporally coherent outputs, i.e., 'maps without gaps ' (e.g.…”
Section: Introductionmentioning
confidence: 99%